Gene expression profiling in the myelodysplastic syndromes. - Pellagatti, A; Fidler, C; Wainscoat, J; Boultwood, J (2005)
The myelodysplastic syndromes (MDS) are a heterogeneous group of haematopoietic malignancies, characterized by blood cytopenias, ineffective hematopoiesis and hypercellular bone marrow. Several genetic alterations have been reported in MDS but these are not MDS-specific and the underlying molecular causes of the disease remain poorly understood. Gene expression microarray technology allows the simultaneous parallel analysis of many thousands of genes and has already provided novel insights into cancer pathogenesis. In this review we discuss the results of several recent studies which utilize the enormous power of microarray technology for the study of MDS. Several exciting findings have emerged from these early studies that highlight the potential of this technology to further our understanding of the molecular pathogenesis of this disorder. It is clear, however, that these findings should be confirmed in larger sets of MDS patients.